Understanding extreme sea levels for broad-scale coastal impact and adaptation analysis - T. Wahl (Nature Portfolio, 2017)
Uncertainties in contemporary extreme sea levels (ESL) from mean sea level rise (SLR) projections have been overlooked in broad-scale risk and adaptation studies. Here, the authors quantify the uncertainties in present-day global ESL estimates and find that they exceed those from global SLR projections.